2007
DOI: 10.1038/sj.jp.7211877
|View full text |Cite
|
Sign up to set email alerts
|

Choice of antenatal testing significantly effects a patient's work obligations

Abstract: Objective: We sought to compare two approaches to antenatal testing for their impact on the workforce.Study Design: This is a prospective observational study of women who presented for antenatal testing. All women were given a survey upon presentation. As per hospital protocol, nonstress testing (NST) was performed semiweekly and biophysical profile (BPP) was performed weekly. The choice of testing was determined by the attending physician. w 2 -and Student's t-tests were performed where appropriate. A P-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These scores improved at 5 minutes in low-risk group but not significantly in high-risk group. [12][13][14][15][16][17][18] Present study found that participants with multipara were noted slightly more among high-risk group compare to low-risk group.…”
Section: Resultsmentioning
confidence: 86%
“…These scores improved at 5 minutes in low-risk group but not significantly in high-risk group. [12][13][14][15][16][17][18] Present study found that participants with multipara were noted slightly more among high-risk group compare to low-risk group.…”
Section: Resultsmentioning
confidence: 86%
“…This literature highlights the health of employed pregnant women as important owing to the growing number of women who continue paid work during pregnancy (Baker 1999; Cooklin et al . 2007; Denney et al . 2008; Higgins et al .…”
mentioning
confidence: 99%